2018
DOI: 10.1186/s12870-018-1496-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis using the Agrobacterium tumefaciens-mediated CRISPR-Cas9 system in common wheat

Abstract: BackgroundRecently, the CRISPR/Cas9 system has been widely used to precisely edit plant genomes. Due to the difficulty in Agrobacterium-mediated genetic transformation of wheat, the reported applications in CRISPR/Cas9 system were all based on the biolistic transformation.ResultsIn the present study, we efficiently applied targeted mutagenesis in common wheat (Triticum aestivum L.) protoplasts and transgenic T0 plants using the CRISPR/Cas9 system delivered via Agrobacterium tumefaciens. Seven target sites in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(48 citation statements)
references
References 52 publications
0
42
0
1
Order By: Relevance
“…CRISPR/Cas9 has been the primary choice for plant genome editing, and Agrobacterium ‐mediated transformation is the most common method for delivery of the CRISPR/Cas9 DNA components to plants (Soyars et al ., ). Mainly due to historical reason, all genome editing systems in wheat were implemented through the biolistics‐mediated transformation (Liang et al ., ; Sánchez‐León et al ., ; Wang et al ., , ; Zhang et al ., ,). Co‐transfer of large DNA fragments from the vector backbone by biolistic transformation leads to the high frequency of transgene silencing (Anand et al ., ; Tassy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CRISPR/Cas9 has been the primary choice for plant genome editing, and Agrobacterium ‐mediated transformation is the most common method for delivery of the CRISPR/Cas9 DNA components to plants (Soyars et al ., ). Mainly due to historical reason, all genome editing systems in wheat were implemented through the biolistics‐mediated transformation (Liang et al ., ; Sánchez‐León et al ., ; Wang et al ., , ; Zhang et al ., ,). Co‐transfer of large DNA fragments from the vector backbone by biolistic transformation leads to the high frequency of transgene silencing (Anand et al ., ; Tassy et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In T 0 plants, deep sequencing indicates that over 99% of the mutations are due to deletions, and our genotyping data from T 1 and T 2 plants show that only five insertions were found of the 68 mutations detected, all of which are insertions of 1‐bp A or T. Remaining 63 mutations are deletions (Figure S11). Similar scenarios were also found in other wheat studies (Liang et al ., ; Sánchez‐León et al ., ; Wang et al ., , ; Zhang et al ., ,). Thus, deletions are the dominant type of edit mutations in wheat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, gene editing has been widely applied to improve the agronomic traits of crops (Wang et al , ; Zhang et al , ). It is possible that this technique can be used to knock out DA1 and its close homologs (Zhang et al , ), potentially generating a much greater impact on wheat kernel size. Furthermore, our proteomic data showed that TaDA1 and TaGW2 affected partially overlapping but relatively independent protein networks involved in diverse pathways (Figure a, b), including protein and starch biosynthesis, cell proliferation, and cell expansion.…”
Section: Discussionmentioning
confidence: 99%